The effects of biomanipulation on the biogeochemistry, carbon isotopic composition and pelagic food web relations of a shallow lake - B. M. Bontes; R. Pel; B. W. Ibelings; H. T. S. Boschker; J. J. Middelburg; E. Van Donk (Biogeosciences, 2006)
In this study we investigated the effects of experimental biomanipulation on community structure, ecosystem metabolism, carbon biogeochemistry and stable isotope composition of a shallow eutrophic lake in the Netherlands. Three different biomanipulation treatments were applied. In two parts of the lake, isolated from the rest, fish was removed and one part was used as a reference treatment in which no biomanipulation was applied. Stable isotopes have proved useful to trace trophic interactions at higher food web levels but until now methodological limitations have restricted species specific isotope analysis in the plankton community. We applied a new approach based on the combination of fluorescence activated cell sorting (FACS) and isotope ratio mass spectrometry (IRMS) to trace carbon flow through the planktonic food web. With this method we aimed at obtaining group specific δ13C signatures of phytoplankton and to trace possible shifts in δ13C resulting from fish removal. Biomanipulation led to an increase in transparency and macrophyte biomass and decrease in phytoplankton abundance, but zooplankton numbers did not increase. Fish removal also resulted in high pH, high O2, low CO2 and more negative δ13CDIC values than expected, which is attributed to chemical enhanced diffusion with large negative fractionation. Despite high temporal variation we detected differences between the isotopic signatures of the primary producers and between the different treatments. The fractionation values of green algae (~21) and diatoms (~23) were similar and independent of treatment, while fractionation factors of filamentous cyanobacteria were variable between the treatments that differed in CO2 availability. 13C-labeling of the phytoplankton groups showed that biomanipulation led to increased growth rates of green algae and diatoms at the expense of cyanobacteria. Finally, consumers seemed generalists to the available food sources.